2001
DOI: 10.1080/09553000110034621
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous, very low-dose gamma-irradiation on the mouse immune system

Abstract: The parameters of cellular immunity studied were not affected by this chronic low-dose of irradiation, but this dose rate is probably too low to induce the hormetic effect previously described. Further investigations are necessary to assess whether the decline of immunoglobulin secretion is indicative of a lower rate of infectious diseases or a defect in B-cell function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Significant decreases in IgG1, IgG2a, and IgG2b were reported in mice exposed to chronic low‐dose γ irradiation (43), but we did not detect a change in IgM transcription in embryos exposed to the ISS radiation environment (Fig. 5 C ).…”
Section: Discussioncontrasting
confidence: 50%
“…Significant decreases in IgG1, IgG2a, and IgG2b were reported in mice exposed to chronic low‐dose γ irradiation (43), but we did not detect a change in IgM transcription in embryos exposed to the ISS radiation environment (Fig. 5 C ).…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies have shown that the mass and leukocyte populations of the spleen are modified when mice are subjected to various types of radiation (41)(42)(43)(44). Significant decreases in IgG1, IgG2b, and IgG2a in mice exposed to chronic low-dose gamma irradiation have also been reported (45).…”
Section: Potential Causes Of the Spaceflight-associated Changes In Vhmentioning
confidence: 87%
“…These findings suggested that the pattern of gene expression in CD4 + T cells was significantly modified after protracted low-dose proton irradiation, with the modifications highly dependent upon the total dose and dose rate of irradiation [115]. Very low dose rate γ-irradiation (100 mGy/year) was also reported to result in a significant decrease in levels of IgG1, IgG2b and IgG2a at 12, 18 and 24 months post irradiation respectively while the total number of B-cells within the spleen remained unchanged [116]. In addition, mouse lymphocytes subjected to LDIR were observed to have increased intracellular calcium ions and stimulated protein kinase C (PKC) activities [117].…”
Section: The Mechanisms For Ldir- or Ldrir-induced Bionegative And Bimentioning
confidence: 99%